A Case of Systemic Lupus Erythematosus diagnosed on bone marrow aspiration - Mukta Pujani; Shivani Kushwaha; Neha Sethi; Anu Beniwal; Shailaja Shukla (Mediterranean Journal of Hematology and Infectious Diseases)
Abstract: